Excess and embodiment in contemporary women's writing - Atayurt, Zeynep Zeren (Studies in English literatures ;, 2014)
The 'obese' female body has often been portrayed as the 'other' to the slender body. However, this process of 'othering', or viewing as different, has created a repressive discourse, where 'excess' has increasingly come to be studied as a 'physical abnormality' or a signifier of a 'personality defect' in contemporary Western society. This book engages with the multifarious re-imaginings of the 'excessive' embodiment in contemporary women's writing, drawing specifically on the construction of this form of embodiment in the works of Fay Weldon, Jeanette Winterson, Margaret Atwood, Claude Tardat,